Snake Bite in Gezira Revision of 63 Envenomed Child - Elbashir, Mohammed Toum; Nug, Faisal A; Mohammed, Osman Taha; Yaseen, Diaa . E; Bader Elmaarif, Mohammed Suror; Mohamed Allam, Tigani Hassan (مجلة الجزيرة للعلوم الصحية; مجلد 8 عدد 1 (2012), 2012)
Sixty three patients admitted to the Gezira National Center of Pediatric Surgery with snake bite were analyzed. All patients were envenomed and the snake was positively identified. In 39 patients (61.9%) the offending snake was (washash) (Echis carinatus) and in 24 patients (38.1%) (Abdafan) (atractaspis microlepidata) was identified. All patients were from rural Gezira where children are actively involved in agriculture and harvesting. The median age group was 9.3 years. Females were equally involved as males. The mean time elapsed since the bite was 56 hours. Quicker arrival at hospital was seen in severe envenomation. Fifty patients had already received native remedies which was observed to increase the local wound complications. Most bites (79%) occurred in the leg .The majority of the bites occurs in the early rainy summer months. All patients presented initially with progressive painful swelling. Local necrosis was observed in seventeen patients (26.9%).  Fourteen patients (22.2%) developed compartment syndrome and three patients (4.76%) developed fingertip gangrene. one patient (1.6%) developed extensive bilateral common iliac vein thrombosis. DIC developed in 21 patients (33.3%). Two patients (3.2%) of theses developed intracranial haemorrhage. Four patients (6.3%) with local necrosis presented few month later with extensive chronic osteomyelitis.Treatment options included cardiovascular support, local wound debridement, fasciotomy and minor amputation. Patients with DIC were managed with fresh frozen plasma, blood transfusion and heparin. Antivenin was not administered to our patients. All patients eventually recovered except one child (1.6%) who succumbed of massive intracerebral haemorrhage. ملخص:  تم تحليل البيانات لثلاث وستين طفلا تم تنويمهم بمركز الجزيرة القومي لجراحة الأطفال في الفترة من مارس 2001م الي ابريل2010م  بعد أن شخصت حالتهم بلدغة ثعبان سام. في كل المرضى تم التعرف على الثعبان, في 39 مريض كان الثعبان اللادغ من نوع و شاش(echis carinatus)  وفي 24 أبو دفان (atractaspis   (micolepidata كل المرضي كانوا أطفالا من أرياف الجزيرة وجميعهم يعمل في الزراعة والحصاد. بلغ متوسط العمر لديهم 9.3 سنة. كانت الإصابة متساوية لدي الذكور والإناث, متوسط الوقت المنصرم منذ اللدغة بالثعبان وحتى ألمجي للمستشفي  كانت 56 ساعة ,لوحظ إن ألمجي الباكر للمستشفي يكون في حالات التسمم الوخيم . المعالجة لهؤلاء المرضي تضمنت مساعدة الجهاز الدوري وانضار الجرح الموضعي و بضع اللفافة وإجراء البتر البسيط ,المرضي اللذين عانوا من التخثر المنتشر داخل الأوعية الدموية تمت معالجتهم بحقن المصورة المتجمدة الطازجة ونقل الدم الطازج واعطا الهبارين. لم يتم استخدام الترياق في أي من المرضي. كل المرضي تماثلوا للشفاء إلا مريضا واحدا توفي بسبب نزف جسيم داخل القحف.